Therapeutic effect of cortistatin on experimental arthritis by downregulating inflammatory and Th1 responses. Issue 5 (6th December 2006) - Gonzalez-Rey, Elena; Chorny, Alejo; Del Moral, Raimundo G; Varela, Nieves; Delgado, Mario
Abstract : Background: Rheumatoid arthritis is a chronic autoimmune disease of unknown aetiology characterised by chronic inflammation in the joints and subsequent destruction of the cartilage and bone. Aim: To propose a new strategy for the treatment of arthritis based on the administration of cortistatin, a newly discovered neuropeptide with anti-inflammatory actions. Methods: DBA/1J mice with collagen-induced arthritis were treated with cortistatin after the onset of disease, and the clinical score and joint histopathology were evaluated. Inflammatory response was determined by measuring the levels of various inflammatory mediators (cytokines and chemokines) in joints and serum. T helper cell type 1 (Th1)-mediated autoreactive response was evaluated by determining the proliferative response and cytokine profile of draining lymph node cells stimulated with collagen and by assaying the content of serum autoantibodies. Results: Cortistatin treatment significantly reduced the severity of established collagen-induced arthritis, completely abrogating joint swelling and destruction of cartilage and bone. The therapeutic effect of cortistatin was associated with a striking reduction in the two deleterious components of the disease—that is, the Th1-driven autoimmune and inflammatory responses. Cortistatin downregulated the production of various inflammatory cytokines and chemokines, decreased the antigen-specific Th1-cell expansion, and induced the production of regulatory cytokines, such as interleukin 10 and transforming growth factor β1. Cortistatin exerted its effects on synovial cells through both somatostatin and ghrelin receptors, showing a higher effect than both peptides protecting against experimental arthritis. Conclusion: This work provides a powerful rationale for the assessment of the efficacy of cortistatin as a novel therapeutic approach to the treatment of rheumatoid arthritis.